The Effect of Addition of EM 4 Starter and Tomato Waste on Organic Compost Formation Rate of Vegetable Waste - Hidayah, Thauhidayatul (SainsTech Innovation Journal, 2018)
Waste problem is a problem faced by humans from ancient times until now. Landfill will cause many problems, especially for people who live around the landfill and landfill. Seeing this fact, it is necessary to make a system of waste management that is effective and efficient. One way is to change the waste from organic material to compost and recycle waste from inorganic materials. This study aims to determine the effect of the addition of EM 4 starter or the addition of tomato waste in accelerating the rate of compost formation from vegetable waste. The design of this study was carried out by an experimental method using a Completely Randomized Design (CRD). The solution used consisted of three different solutions namely 100 ml / 1 l distilled tomato solution, 100 ml / 1 l distilled EM-4 solution, and 100 ml / 1 l distilled tomato + EM-4 solution. The third solution is mixed into vegetable waste in a polybag. The parameters observed consisted of compost, namely time / average time of compost formation, pH, temperature, change in compost weight, and organoleptic test. The parameters were observed once a week for 4 weeks. Based on data analysis using one way ANOVA, the results obtained from the treatment of tomato + EM 4 waste formed the fastest compost, 29.5 days, pH 7 (normal), temperature 30 ?, and final weight of compost 220 gr, and organoleptic yield of 54.375%. This can occur because tomato waste is one type of organic waste that can be used as a culture medium (inoculants) containing microbes that are able to degrade organic materials. Based on this research, it can be concluded that the addition of EM-4 and tomato waste as well as a mixture of both can accelerate the rate of compost formation.